1994
DOI: 10.1182/blood.v84.1.133.bloodjournal841133
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-associated forms of the beta A4 amyloid protein precursor of Alzheimer's disease in human platelet and brain: surface expression on the activated human platelet

Abstract: The amyloid protein precursor (APP) of Alzheimer's disease (AD) is abundantly expressed in platelets, where its primary function remains undetermined. As an integral transmembrane protein, the release of APP from the membrane may be a critical event in AD. We examined the association of APP with human platelet membranes using a combination of alkali treatment and immunoprecipitation of the carboxyl-terminus of APP. Most of the platelet membrane-associated APP (APPMem) with molecular mass of 100 to 130 kD is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Although this mouse model have been widely use to investigate neuronal dysfunctions, little information is available on the consequences of these mutations on circulating blood cells, including platelets. Platelets express high level of APP [36]. We demonstrated that platelet and white blood cell number in 3xTg-AD mice are normal compared to WT (figure 1B and C).…”
Section: Normal Platelet Count and Glycoprotein Expression In 3xtg-admentioning
confidence: 67%
“…Although this mouse model have been widely use to investigate neuronal dysfunctions, little information is available on the consequences of these mutations on circulating blood cells, including platelets. Platelets express high level of APP [36]. We demonstrated that platelet and white blood cell number in 3xTg-AD mice are normal compared to WT (figure 1B and C).…”
Section: Normal Platelet Count and Glycoprotein Expression In 3xtg-admentioning
confidence: 67%
“…35,39 Human platelets are known to be the source of more than 90% of circulating PPA protein [40][41][42] and store Aβ in their granules, especially Aβ40, stimulated by physiological agonists such as thrombin, collagen or calcium. 40,[43][44][45] Investigations have been carried out into the expression of platelets in AD patients, showing alterations during some stages of the disease. The proportion of two isoforms, APP protein products that occur in platelets, was studied as a potential biomarker and was decreased in the platelet membranes of patients with AD and MCI when compared to control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In AD, however,  and -secretases activity increases, and APP is metabolized to produce amyloid  peptides, which leads to alteration of the APP content of platelets (10). Soluble APP fragments and A peptides are stored in platelet granules and released upon stimulation with physiological agonists (11). Several studies suggested that platelet-derived A peptides may represent a reliable peripheral biomarker of AD (12,13).…”
Section: Introductionmentioning
confidence: 99%